Evaluation of Transformer Core and Winding Conditions from SFRA Measurement Results using Statistical Techniques for Distribution Transformers - Ab Ghani, Sharin; Md Thayoob, Yasmin Hanum; Yang Ghazali, Young Zaidey; Ahmad Khiar, Mohd Shahril; Sutan Chairul, Imran (2012)

(untitled)
Distribution transformers in TNB (Tenaga Nasional Berhad) Malaysia are exposed to thermal and electrical stresses. Those stresses are effecting the main mechanical active parts in transformer such as core and winding. In field, lightning strikes and cable faults may cause problem due to transformer core and winding. SFRA diagnosis is made based on the comparison between two SFRA responses and any significant difference in low, middle and high frequency sub-bands region would potentially indicate mechanical or electrical problem due to core and winding of transformer. Instead of using graphical comparison, statistical techniques such as Cross-correlation Coefficient Function (CCF), Standard Deviation (SD) and Absolute Sum of Logarithmic Error (ASLE) can be used to interpret the SFRA results in a proper way. The aim of this paper is to evaluate the condition of TNB distribution transformer by using SFRA method in line with the interpretation from the statistical techniques.